Let a quadratic equation be represented as
A ( 3 − 2 ) x 2 + ( 3 + 2 ) B x + C = 0 ,
where A = ( 4 9 + 2 0 6 ) 1 / 4 and B = 8 3 + 3 8 6 + 3 1 6 + . . . . .
Let α and β be the roots of the above equation which are related to the constraint ( ∣ α − β ∣ = ( 6 6 ) k ,
where k = lo g 6 1 0 − 2 lo g 6 5 + lo g 6 lo g 6 1 8 + lo g 6 7 2 .
Find the value of C .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nilesh u should make a set of your YET ANOTHER EASY QUESTION ! and link it to your questions like Aniket
Problem Loading...
Note Loading...
Set Loading...
A = ( ( 2 4 + 2 5 ) 2 ) 1 / 4 = ( ( 3 + 2 ) 2 ) 1 / 2 = 3 + 2 B is a sum of Infinite GP with r = 3 6 . B = 1 − 3 6 8 3 = 3 − 2 2 4
Hence equation is : x 2 + 2 4 x + C = 0
Using property lo g a b + lo g a c = lo g a b c , k = lo g 6 1 0 − lo g 6 5 + lo g 6 4 = lo g 6 4
We note ( α − β ) 2 = ( α + β ) 2 − 4 α β = 5 7 6 − 4 C (Using Vieta’s)
( 6 3 / 2 ) k = ( 6 lo g 6 4 3 / 2 ) = 8
Hence, 5 7 6 − 4 C = 6 4 ⟹ C = 1 4 4 − 1 6 = 1 2 8